2018
DOI: 10.5937/sestrec1877009m
|View full text |Cite
|
Sign up to set email alerts
|

Pušenje kao faktor rizika za nastanak kardiovaskularnih bolesti kod zdravstvenih i prosvetnih radnika Crne Gore

Abstract: ¹Visoka medicinska škola Berane,²Srednjoškolski centar Foča, ³Klinički centar Crne Gore, ⁴Medicinski fakultet Podgorica, ⁵Medicinski fakultet Podgorica APSTRAKT UVOD: Godišnje više ljudi umre od kardiovaskularnih bolesti (KVB) nego od bilo kog drugog uzroka. Faktori rizika u nastanku KVB su mnogobrojni i imaju kumulirajući efekat.Rezultati dosadašnjih studija pokazuju da pušenje cigareta ima ključnu ulogu u razvoju KVB. CILJ ISTRAŽIVANJA: Utvrditi uticaj pušenja, kod zdravstvenih i prosvjetnih radnika, na nast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The results showed that the main inhibiting factors of good communication are, first of all, personal characteristics such as fear, low self-confidence, anxiety, level of literacy, previous experiences and, on the other hand, lack of communication skills, empathy, inability to set boundaries, listening skills, and the environment. (10) The results also show that the use of good communication has not only a positive impact on patients, but also on health professionals, making them satisfied at work, less exposed to stress, which has a strong impact on health. Job satisfaction and leadership style are closely related.…”
Section: Introductionmentioning
confidence: 83%
“…The results showed that the main inhibiting factors of good communication are, first of all, personal characteristics such as fear, low self-confidence, anxiety, level of literacy, previous experiences and, on the other hand, lack of communication skills, empathy, inability to set boundaries, listening skills, and the environment. (10) The results also show that the use of good communication has not only a positive impact on patients, but also on health professionals, making them satisfied at work, less exposed to stress, which has a strong impact on health. Job satisfaction and leadership style are closely related.…”
Section: Introductionmentioning
confidence: 83%